Granulomatosis with polyangiitis presenting as facial nerve palsy in a teenager. (April 2018) - Wang, James C.; Leader, Brittany A.; Crane, Ryan A.; Koch, Bernadette L.; Smith, Matthew M.; Ishman, Stacey L.
Abstract: Granulomatosis with polyangiitis (GPA, previously known as Wegener's granulomatosis) is an autoimmune systemic small-vessel vasculitis, associated with the presence of anti-neurophil cytoplasmic antibodies with a cytoplasmic staining pattern (c-ANCA). It is characterized by necrotizing granulomas, usually affecting the airways and kidneys. GPA should be considered when patients do not improve despite adequate treatment of otologic symptoms, when patients have unspecific symptoms suggesting systemic disease (e.g. fever, malaise), or when other organs are involved (kidney, lungs, etc.). We present an interesting case of a 14-year-old female with eight-weeks of bilateral otalgia, unilateral facial nerve palsy, decreased appetite, and fatigue refractory to steroid, anti-viral, and antibiotic treatment ultimately diagnosed with GPA.